PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP RETURN ON INVESTMENT (ROI) PADA LQ45 YANG TERDAFTAR DI BURSA EFEK INNDONESIA - arif defri artanto; Iskandar Iskandar; Indra Suyoto Kurniawan (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
ArifDefriArtanto, Influence of Cash Turnover and Receivable Turnover on Return On Investment (ROI) in LQ45 Companies Listed on the IDX. Guided by Iskandar as the first supervisor and Indra Sutoyo Kurniawan as the second supervisor.This study aims to analyze and determine the effect of cash turnover and account receivable turnover on return on investment. The type of research used in this study is quantitative, namely data in the form of numbers or data that can be calculated and can be analyzed systematically. Quantitative data in this study are the numbers contained in cash flows and accounts receivable and other data that can be found in the company's financial statements. These data are sourced through secondary data, and the techniques used in data collection use the method of observation and library research.The results of this study are 1. Partially cash turnover has an effect on Return On investment. While 2. Account receivable turnover does not partially affect Return On investment.